Hypoglycemic effect of the polyphenols rich extract from Rose rugosa Thunb on high fat diet and STZ induced diabetic rats. (22nd March 2017) - Liu, Liu; Tang, Dan; Zhao, Haiqing; Xin, Xuelei; Aisa, Haji Akber
Abstract: Ethnopharmacological relevance: Rosa rugosa Thunb is a traditional Uygur medicine that has been used in the treatment of diabetes in Uygur ancient recipe for hundreds of years. However, the mechanism of Rosa rug osa Thunb activity is still unclear. This study was designed to address this issue by studying the polyphenols enriched extract (RPE) of Rosa rugosa Thunb in diabetic rats. Materials and methods: RPE were tested in the inhibition of α-glucosidase and oxidative stress in vitro . RPE was administrated at dosages of 37.5, 75 and 150 mg/kg body weight in the type 2 diabetic rats, which were made by high fat diet feeding plus a low dose of STZ injection (30 mg/kg). The therapeutic effect was evaluated four weeks later. Oral glucose tolerance test (OGTT), insulin tolerance test (ITT) and insulin signal pathway (PI3K/AKT) were examined to determine insulin sensitivity. Blood glucose levels and body weight were measured weekly in the study. Results: In vitro, RPE exhibited an activity in the inhibition of α-glucosidase and had an excellent antioxidant activity in the liver of diabetic rats. RPE significantly decreased the fasting blood glucose, improved insulin sensitivity (HOMA-IR), OGTT, ITT and blood lipid profile. The glycogen synthesis and hexokinase activity were increased together with the improved signaling activity of insulin as indicated by p-IRS, p-IR, p-AKT, and p-GSK-3β. Conclusions: The results suggest that RPE reduced blood glucose in type 2 diabetic rats by improvement of insulin sensitivity. The effect is likely achieved by inhibition of oxidative stress and α-glucosidase. Graphical abstract: